Buying and Selling Followers in the View of National Law and Fatwa of the Indonesian Ulema Council: Comparative Study - Kurniati; Imran, Muh. Fadhil Abdillah; Aris, Aryan (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2023)
The provisions for the implementation of electronic transactions related to buying and selling followers are contained in article 18 which states that if the sale is carried out via the internet, the contract must be in the form of an electronic agreement that is legally binding. The jurists of the Hambali, Hanafi and al-Shafi'i madhhabs say that the object of the contract must be deliverable, the object must be present at the time the contract is performed, and it must not sell something that does not exist such as unfinished fruit (ripe). In contrast to the Maliki Madhhab which allows the buying and selling of immature fruit, on the basis that the immature part is included in the fruit that has already appeared, and only requires that the object must be present at the time of contract at the time of sacrifice of the fruit. In contrast to the view of law number 11 of 2008 where the provisions for the implementation of electronic transactions related to buying and selling followers are contained in article 18 which reads that if the sale is carried out via the internet, the contract must be in the form of an electronic agreement that is legally binding, then the applicable law must be in accordance with the basic principles of international criminal law and there are exceptions in article 20, namely in electronic agreements that With regard to the decision of both parties in relation to the agreement on the execution of the agreement, then the electronic transaction takes place only if the buyer has agreed and accepted the seller's offer. This research is included in the category of library research and uses methodology in the form of juridical, shari'i and sociological approaches. The data sources used are primary data sources, namely hadith, Qur'anic verses and the views of madhab imams while secondary data sources are journals, library books, data collected through reading, studying, and collecting a number of references related to the material. The journal of this study is, sellers and buyers who buy and sell followers to make an agreement before the contract is closed